Association between cardiovascular health and markers of liver function: a cross-sectional study from NHANES 2005–2018 - Yu, Huang; Zhang, Tingyi; Liu, Yankun; Wang, Wang; Guan, Ziyi; Li, Ping (Frontiers in Medicine, 2025)
BackgroundCardiovascular health (CVH) has been associated with various systemic diseases. However, the relationship between CVH, as measured by Life’s Essential 8 (LE8), and liver function markers in the general population remains poorly understood.MethodsThis study analyzed data from 21,156 participants (aged ≥ 20) from the NHANES 2005–2018 to investigate the associations between CVH and liver function markers [alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transferase (GGT), alkaline phosphatase (ALP), albumin and AST/ALT ratio]. Linear regression models were used, along with a restricted cubic spline (RCS) to assess dose-response. Weighted quantile sum (WQS) regression and quantile g-computation (QGC) analyses were employed to evaluate the association between CVH and liver function markers.ResultsLinear regression analysis showed that each 1-point increase in CVH score was significantly associated with decreased levels of liver enzymes [ALT: −0.200 U/L (95% CI: −0.223, −0.176), AST: −0.043 U/L (−0.062, −0.024), GGT: −0.453 U/L (−0.509, −0.397), ALP: −0.310 U/L (−0.340, −0.281)] and increased levels of albumin [0.040 g/dL (0.036, 0.045)] and AST/ALT ratio [0.0056 (0.0051, 0.0061)]. Notably, CVH score demonstrated non-linear dose-response relationships with ALT, ALP, and AST/ALT ratio. Age significantly modified these associations, while nicotine exposure, BMI, and blood lipids were identified as primary contributors through WQS and QGC analyses. E-value analysis suggested robustness to unmeasured confounding.ConclusionThis study demonstrates robust associations between CVH and liver function markers in United States adults, with nicotine exposure, BMI, and blood lipids identified as significant contributors. These findings suggest that maintaining optimal cardiovascular health may have beneficial effects on liver function, highlighting potential targets for integrated prevention strategies.